Do Environmental, Social, and Governance (ESG), Leverage, and Financial Performance Affect Tax Avoidance? - Sugimin; Indarto; Indudewi, Dian (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2024)
This research aims to test the effect of Environmental, Social, and Governance (ESG) proxied by ESG Risk Rating on tax avoidance. This study also examines the influence of leverage measured by the Debt-to-Assets Ratio (DAR) on tax avoidance. Moreover, this research also examines the effect of financial per-formance as sized by the Return on Assets Ratio (ROA) on tax avoidance. This study uses quantitative descriptive research and panel data analysis to scrutinize data from companies listed in the ESG Leaders Index over three years from 2020 to 2022. The research used eViews 12 software to analyze a descriptive-quan-titative panel data regression analysis to evaluate the research hypotheses. The result showed that imple-menting ESG can reduce tax avoidance and create better financial performance. However, leverage is proven to reduce tax avoidance, but does not influence financial performance. This research concludes that tax avoidance isn’t affected by financial performance but is more influenced by management be-havior. Moreover, financial performance does not mediate the relationship between ESG, leverage, and tax avoidance. These findings underscore the importance of integrating sustainability principles into cor-porate governance to mitigate tax avoidance behaviors and promote fiscal transparency.